2022
DOI: 10.1186/s40795-022-00532-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malnutrition and associated factors among older adults from urban and rural residences of Metu district, Southwest Ethiopia

Abstract: Background In Ethiopia, the proportion of older adults is steadily increasing. This rapidly growing older adult population may increase the burden of malnutrition. However, malnutrition among older adults, particularly those living in rural areas, is regularly underrecognized and/or ignored. There have been no studies among older adults in the Metu district that have used the Min nutritional assessment (MNA). As a result, the purpose of this study is to determine the prevalence of malnutrition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Several reports have shown that the prevalence of malnutrition in rural communities is approximately double that in urban communities because rural older adults have less access to healthcare services, family support, and diverse food options. 41,42 Therefore, our results indicate the need for screening and early interventions for malnutrition and the risk of malnutrition among rural older Vietnamese adults.…”
mentioning
confidence: 75%
“…Several reports have shown that the prevalence of malnutrition in rural communities is approximately double that in urban communities because rural older adults have less access to healthcare services, family support, and diverse food options. 41,42 Therefore, our results indicate the need for screening and early interventions for malnutrition and the risk of malnutrition among rural older Vietnamese adults.…”
mentioning
confidence: 75%
“…(8)(9)(10) In Ethiopia, undernutrition among the elderly population is a common health problem and its magnitude range from 15⋅7 to 40⋅2 %. (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) Nutritional deficiencies in older persons have serious negative consequences which can increase morbidity and mortality, hospitalisation, development of ulcers, and infections. (12) Involuntary weight loss can result in a reduction in the ability to care for oneself, loss of mobility and independence, and a poorer quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of malnutrition among elderly people in different countries of the world varies between 10% and 60% (Abate et al, 2020; Konda et al, 2018; Tessfamichael et al, 2014). Malnutrition among older persons is common in Ethiopia, and it remains one of the country's significant public health issues (Abate et al, 2020; Ferede et al, 2022; Kushwaha et al, 2020; Tessfamichael et al, 2014; Wondiye et al, 2019). Studies recommended that further nutrition education intervention is the best strategy to prevent and manage malnutrition among the elderly so that they can achieve a better quality of life and health as they age (Bandura, 1986; Gezahegn et al, 2016; Paul et al, 2022; Poda et al, 2019).…”
Section: Introductionmentioning
confidence: 99%